Madagascar : Reforming Land Administration and Management for Equitable Growth and Social Cohesion - World Bank (Washington, DC, 2017)
A well-functioning land administration and management system is crucial for Madagascar's economic and social future. Land is implicated in Madagascar's ongoing economic development and social transformation in many important ways, as key a factor in its quest for economic growth, urbanization, transparent decision-making on land-related foreign investments, environment protection, vibrant and sustainable rural communities, political stability, and social cohesion. Striking a balance among different, and sometimes even competing, roles played by land in the economic and social development process is a daunting challenge facing the Government. It is not an exaggeration to argue that soundness of land administration and management system will play a crucial role in determining the shape and trajectory of Madagascar's economic and social future. Madagascar's quest for overall economic growth, urbanization, sustainable rural development, environment protection, and social cohesion calls for a transparent, inclusive, equitable, efficient, and service-oriented land administration and management system. This policy note presents six policy recommendations aiming to help the Government to continue and deepen land tenure reform. All these six policy recommendations are made based on a review of the history of the Malagasy land institution, an assessment on the implementation of the national land tenure reform program since 2005, and an examination on the major remaining land-related challenges. International experiences have also been introduced whenever they are relevant. It is believed that now is a good time for the Government of Madagascar to tackle these challenges and consider these policy recommendations.